Uncertainty model of electro-optical thrombus growth estimation for early risk detection. (February 2016) - Affanni, A.; Chiorboli, G.; Specogna, R.; Trevisan, F.
Highlights: New method for 3D image of thrombi formation with optical and impedance data fusion. The method allows estimating the time evolution of the 3D thrombus geometry. The uncertainty model for the thrombus geometry reconstruction is provided. State-of-the-art optical instruments do not allow the time evolution of 3D images. Abstract: It is proposed a device for the study of the real-time aggregation of white thrombi in whole blood. This device allows extrapolating the 3D-shape of platelets clotting within artificial capillaries, by simultaneously monitoring the electrical impedance between a pair of specifically designed gold electrodes and 2D optical image of pixel luminance of the fluorescent labeled platelets. Up to 30 3D images per minute have been obtained, for a process which requires few minutes before the aggregation of large thrombi structures, a noticeable result with respect to other 3D-shape reconstruction methods. The contribution of this paper mainly consists in the study of an uncertainty model which, in our opinion, is of fundamental importance to provide a valuable metrological estimation of thrombus growth under flow conditions.